Impact of a Quality Improvement Project on Deceased Organ Donor Management. (December 2015) - Olmos, Andrea; Feiner, John; Hirose, Ryutaro; Swain, Sharon; Blasi, Annabel; Roberts, John P.; Niemann, Claus U.
Context—: Donors showed poor glucose control in the period between declaration of brain death and organ recovery. The level of hyperglycemia in the donors was associated with a decline in terminal renal function. Objective—: To determine whether implementation of a quality improvement project improved glucose control and preserved renal function in deceased organ donors. Methods—: Data collected retrospectively included demographics, medical history, mechanism of death, laboratory values, and data from the United Network for Organ Sharing. Results—: After implementation of the quality improvement project, deceased donors had significantly lower mean glucose concentrations (mean [SD], 162 [44] vs 212 [42] mg/dL; P < .001) and prerecovery glucose concentration (143 [66] vs 241 [69] mg/dL; P < .001). When the donor cohorts from before and after the quality improvement project were analyzed together, mean glucose concentration remained a significant predictor of terminal creatinine level ( P < .001). Multivariate analysis of delayed graft function in kidney recipients matched to donors indicated that higher terminal creatinine level was associated with delayed graft function in recipients ( P < .001). Conclusion—: The quality improvement project improved donor glucose homeostasis, and the data confirm that poor glucose homeostasis is associated with worsening terminal renal function.